Peptides as triggers of plant defence - Albert, Markus (Journal of Experimental Botany, 2013)
Plants are confronted with several biotic stresses such as microbial pathogens and other herbivores. To defend against such attackers, plants possess an array of pattern recognition receptors (PRRs) that sense the danger and consequently initiate a defence programme that prevents further damage and spreading of the pest. Characteristic pathogenic structures, so-called microbe-associated molecular patterns (MAMPs), serve as signals that allow the plant to sense invaders. Additionally, pathogens wound or damage the plant and the resulting release of damageassociated molecular patterns (DAMPs) serves as a warning signal. This review focuses on peptides that serve as triggers or amplifiers of plant defence and thus follow the definition of a MAMP or a DAMP. © The Author 2013. Published by Oxford University Press on behalf of the Society for Experimental Biology. All rights reserved.
CRIS-Team Scopus Importer:2020-03-09
Keywords: Damage-associated molecular pattern; Ligand-receptor interaction; Microbe-associated molecular pattern; Pattern recognition receptors; Peptide ligand; Plant defence; Plant immunity